2017
DOI: 10.1111/jvim.14887
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Epidural Pathology between Cervical and Thoracolumbar Intervertebral Disk Extrusions in Dogs

Abstract: BackgroundAlthough the basic pathophysiology is the same in both cervical and thoracolumbar intervertebral disk (IVD) extrusions, there are considerable clinical differences that have only been partially explained.Hypothesis/ObjectivesThe epidural inflammatory response differs between cervical and thoracolumbar IVD extrusions.AnimalsFifty‐five dogs with cervical and 80 dogs with thoracolumbar IVD extrusions.MethodsClinical data and histopathologic variables were investigated. Associations between severity of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
(120 reference statements)
2
18
0
1
Order By: Relevance
“…Although no histopathological examination was performed to prove that the compressive material seen on MRI was degenerated disc material, it had the same appearance on MRI as cervical HNPE: midventral extradural spinal cord compression because of material with the characteristic “seagull”‐like shape and hyperintense appearance in comparison to spinal cord parenchyma in T2w and fat suppression short tau inversion recovery sequences (STIR; Figure C‐cc). Another study found significant less mineralization of extruded disc material in the cervical than in the thoracolumbar spinal column. The authors proposed that variances in biomechanical, biochemical, and metabolic aspects of the intervertebral discs at different locations were responsible for different amounts of degeneration in the cervical and thoracolumbar intervertebral discs .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although no histopathological examination was performed to prove that the compressive material seen on MRI was degenerated disc material, it had the same appearance on MRI as cervical HNPE: midventral extradural spinal cord compression because of material with the characteristic “seagull”‐like shape and hyperintense appearance in comparison to spinal cord parenchyma in T2w and fat suppression short tau inversion recovery sequences (STIR; Figure C‐cc). Another study found significant less mineralization of extruded disc material in the cervical than in the thoracolumbar spinal column. The authors proposed that variances in biomechanical, biochemical, and metabolic aspects of the intervertebral discs at different locations were responsible for different amounts of degeneration in the cervical and thoracolumbar intervertebral discs .…”
Section: Discussionmentioning
confidence: 93%
“…Another study found significant less mineralization of extruded disc material in the cervical than in the thoracolumbar spinal column. The authors proposed that variances in biomechanical, biochemical, and metabolic aspects of the intervertebral discs at different locations were responsible for different amounts of degeneration in the cervical and thoracolumbar intervertebral discs . These findings are consistent with the local occurrence of HNPE more frequently reported in the cervical region and consisting of less calcified disc material.…”
Section: Discussionmentioning
confidence: 93%
“…Histopathological studies of extruded disc material from dogs have been published previously [2529], but to the authors’ knowledge, only one study [25] concerns specimens obtained exclusively from dachshunds. However, in that study inflammation was well described while information about mineralization is not included.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that study inflammation was well described while information about mineralization is not included. In other histopathological studies [2629], the percentage of dachshunds from which disc material is collected, ranges from 9.1 [29] to 51.1 [26]. In the study with the highest percentage [26], specimens were obtained intraoperatively from a total of 45 dogs, of which 23 (51.1%) were dachshunds.…”
Section: Discussionmentioning
confidence: 99%
“…MRI was performed with a high ield unit (1.5 T, Intera, Phillips Medical Systems) under general anaesthesia. Guidelines for the MRI characterisation of intervertebral disc extrusion (IVDE), [15][16][17][18] intervertebral disc protrusion (IVDP), 17 19 neoplasms 9 20-22 and SM 23 24 were used in making a radiological diagnosis. Cases of osseousassociated and disc-associated CSM were grouped together and diagnosed based on previously reported MRI criteria.…”
Section: Methodsmentioning
confidence: 99%